Rabies encephalitis in a preschool child following postexposure prophylaxis. - K M Chaitra (Public Library of Science (PLoS), 2021)
We report a case of rabies encephalitis in a 4½-year-old male child with an exposure to a suspect rabid dog. The child developed rabies 25 days after receiving postexposure prophylaxis. Rabies immunoglobulin (RIG) is currently administered according to body weight. In high-risk exposures over the head and neck, local administration of RIG over and above the body weight depending on the site, size, and severity of exposure may help to prevent rabies death. There is a need for further studies to generate new evidence in this regard.